Telegram from Max Bredig to Georg Bredig, January 1940 - Bredig, Max Albert (1940)
Telegram from Max Albert Bredig (1902-1977) to his father Georg Bredig (1868-1944). Max tells his father that he should buy a ticket for January 20th, 1940 from either Zaandam or Noordam.
Keywords: Bredig, Georg, 1868-1944; Bredig, Max Albert, 1902-1977; Telegraph; Netherlands--Zaandam; Emigration and immigration